Analisis Masalah –Masalah Belajar Yang Di Alami Oleh Siswa Kelas Akselerasi Dan Unggulan Di SMP Negeri Kota Dumai - Zulfan Saam; Elni Yakub (Jurnal Pendidikan, 2012)
The Purpose of this research is to analyze the study problems subjected to junior highschool students. In particular, the students who being object of this research are student in accelerationclass program and student in excellent class program. This research is based on descriptive analysis andquestionnaire is used as tools with respect to data gathering purpose. Total sample is 123 students andcollected by using census technique. The collected data are then analyzed according to descriptiveanalysis scheme in form of percentage. Result shows that study problem encountered by both student inacceleration and excellent class are study behavior and habits. Elaboration of these problems forstudents in acceleration class leads to three main causes i.e. hard to maintain focus, lack of durabilityduring working on tasks and study. While for students in excellent class program are lacks of responseduring teaching process, incomplete of notes, and hard to understand the text book. Overall resultshows that students in excellent class program are encounter higher percentage of study problemscompare to students in acceleration class program. It can be concluded that students in excellent classprogram having more study problem compare to the studens in acceleration class program.